Model Pembelajaran Mind Mapping Kelas VII Pada Mata Pelajaran Akidah Akhlak Di MTs Az-Zikra Kota Sorong - Irma Al Hamid; Agus Yudiawan (IAIN Sorong, 2018)
Morals in presenting subject matter are sometimes monotonous. Teachers are more likely to use the lecture method in learning, thereby making students bored. Therefore, researchers chose one cooperative learning model, namely the Mind Mapping learning model to improve student learning outcomes. This model uses a grouping system consisting of 2-5 people, which in the implementation stage includes the discussion stage, thinking together to express ideas from the problem concept given by the teacher, asking questions, and answering questions. This study aims to determine the increase in learning outcomes in the subjects of Islamic Morals through the Mind Mapping learning model. This type of research is Classroom Action Research conducted in 2 cycles, namely Cycle I conducted 2 meetings and Cycle II 2 meetings. The subjects of this study were students of Class VII MTs Az-Zikra, Sorong City in the odd semester of the 2016-2017 academic year of 21 students. The object of research is student learning outcomes which are divided into three domains, namely cognitive, affective and psychomotor. Data collection techniques used were observation and tests. The collected data were analyzed both qualitative and quantitative data. Qualitative data is data in the form of a sentence that gives a description of student expressions, the level of understanding of a subject, the learning process takes place and the like. While quantitative data uses descriptive statistical analysis with the application of SPSS 16.0, for example, finding an average value. The results of research based on the cognitive domain showed that there was an increase in the learning outcomes of the moral creed ie from the average value of student learning outcomes in Cycle I was 67.43 (low category) and in Cycle II amounted to 74.52 (low category) but there was an increase in the Cycle I. In Cycle I the number of students who finished as many as 9 people (42.85%), while in Cycle II it increased to 15 people (71.42%), and students who completed had reached 71.42% exceeding the expected target ie 65%. The affective domain looks changes after the teaching and learning process, both from the attitudes, behavior, interests, emotions, motivation, cooperation and coordination of each student which is done through direct observation and interaction. The psychomotor domain is seen from the results of observations or activities of students obtained during the learning process, such as asking questions, answering, responding, dare to submit opinions and draw conclusions from the material that has been submitted. Based on these results it can be concluded that there is an increase in learning outcomes of moral subjects in Sorong City Az-Zikra Class VII students after learning by using Mind Mapping Learning Model.